1998
DOI: 10.1016/s0921-4526(97)00454-7
|View full text |Cite
|
Sign up to set email alerts
|

Cooper-pair delocalization in disordered media

Abstract: We discuss the effect of disorder on the coherent propagation of the bound state of two attracting particles. It is shown that a result analogous to the Anderson theorem for dirty superconductors is also valid for the Cooper problem, namely, that the pair wave function is extended beyond the singleparticle localization length if the latter is large. A physical justification is given in terms of the Thouless block-scaling picture of localization. These arguments are supplemented by numerical simulations. With i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, there the studies were mainly addressed to the properties of excited states while here we will investigate only the properties of the ground state in the case of an attractive interaction. We also note that the attractive case in one-dimension was discussed in [22,23].…”
Section: Ground State Properties Without Magnetic Fieldmentioning
confidence: 94%
“…However, there the studies were mainly addressed to the properties of excited states while here we will investigate only the properties of the ground state in the case of an attractive interaction. We also note that the attractive case in one-dimension was discussed in [22,23].…”
Section: Ground State Properties Without Magnetic Fieldmentioning
confidence: 94%
“…Arau ´jo et al considered the Cooper problem and found that near the ground state an attractive interaction led to delocalization for small disorder while it enhanced localization for large disorder [117].…”
Section: Eigenstatesmentioning
confidence: 99%